2018
DOI: 10.1016/j.jsxm.2018.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Variability in Prices for Erectile Dysfunction Medications—Are All Pharmacies the Same?

Abstract: Background Variability in prices of medications is a well-known phenomenon; however, this variability has not been quantified in the realm of erectile dysfunction (ED) medications. ED medications are ideal for this quantification, because they are often not covered by insurances; therefore, the cost is the most direct reflection of price variability among pharmacies as they affect the patients. Aim To evaluate the variability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…DTC service users were also equally likely to have seen a physician in the prior year, indicating the presence of an established patient-physician relationship that could have been leveraged for men’s health care. Instead, these men opted for care through a DTC platform despite the potentially higher cost of medications compared to traditional prescribing routes or coupon sites [ 18 ]. This may be explained by the perceived savings of DTC services, as many companies advertise comparable medication costs, but often charge additional consultation, membership, and shipping fees.…”
Section: Discussionmentioning
confidence: 99%
“…DTC service users were also equally likely to have seen a physician in the prior year, indicating the presence of an established patient-physician relationship that could have been leveraged for men’s health care. Instead, these men opted for care through a DTC platform despite the potentially higher cost of medications compared to traditional prescribing routes or coupon sites [ 18 ]. This may be explained by the perceived savings of DTC services, as many companies advertise comparable medication costs, but often charge additional consultation, membership, and shipping fees.…”
Section: Discussionmentioning
confidence: 99%
“…16 Accordingly, Mishra et al showed that undiscounted cash prices for four commonly used erectile dysfunction medications were the highest at chain pharmacies. 17 As for brandname CV medications, the GoodRx coupons appear to offer only marginally lower prices compared to undiscounted cash price.…”
Section: Discussionmentioning
confidence: 99%
“…Independent pharmacies may offer patients the most affordable cash prices without any specific discount coupons. 16,17 Aurora et al showed that prices with GoodRx coupons were comparable with cash undiscounted prices at independent pharmacies, whereas, Luo et al found independent pharmacies to have significant price variability and higher average prices on the GoodRx platform. 7 Anecdotally, independent pharmacies may refuse to accept a GoodRx coupon because the company charges the pharmacies an exorbitant processing fee that often results dispensing prescription at a loss.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,22e24 However, our study is the first to identify significant price reductions in lower income neighborhoods. Mishra 13 and Theisen 14 et al identified significantly higher cash prices for ED and BPH medication at chain pharmacies in the Cleveland and Pittsburgh areas, respectively. However, no prior study has focused on socioeconomically disparate neighborhoods such as UES and EH.…”
Section: Discussionmentioning
confidence: 99%
“…12 Previous studies have identified significant variations in the cost of generic medications, reporting increased prices at chain pharmacies compared to independent pharmacies for ED and BPH medications. 13,14 Other studies, however, have shown contrary evidence that independent pharmacies offer higher prices for prescriptions, 15 and that higher pharmaceutical prices may be associated with lower socioeconomic neighborhoods, 16 suggesting a need for further evaluation of these trends. No study has focused on specific urban neighborhoods with significantly different median household incomes.…”
mentioning
confidence: 99%